2015
DOI: 10.1016/j.celrep.2015.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Spatiotemporal Dynamics of Light and Heat Propagation for In Vivo Optogenetics

Abstract: Summary Despite the increasing use of optogenetics in vivo, the effects of direct light exposure to brain tissue are understudied. Of particular concern is the potential for heat induced by prolonged optical stimulation. We demonstrate that high intensity light, delivered through an optical fiber, is capable of elevating firing rate locally, even in the absence of opsin expression. Predicting the severity and spatial extent of any temperature increase during optogenetic stimulation is therefore of considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
375
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(404 citation statements)
references
References 41 publications
26
375
3
Order By: Relevance
“…Most of these data have considered solely the excitation in the blue-green range [23,48] in the rodent brain. In a previous work, we studied exper imentally in vivo in rodents the minimally invasive photostimulation using a fiber (0.4 mm diameter and a 0.48 NA) with 5 ms pulses of 638 nm light with a power varying from 100 to 600 mW mm −2 and a frequency varying from 20 to 60 Hz [49]. We observed a maximum temperature rise of about 0.1 °C to 2.5 °C depending on the experimental parameters.…”
Section: What Is the Expected Temperature Rise And How May It Affectmentioning
confidence: 99%
“…Most of these data have considered solely the excitation in the blue-green range [23,48] in the rodent brain. In a previous work, we studied exper imentally in vivo in rodents the minimally invasive photostimulation using a fiber (0.4 mm diameter and a 0.48 NA) with 5 ms pulses of 638 nm light with a power varying from 100 to 600 mW mm −2 and a frequency varying from 20 to 60 Hz [49]. We observed a maximum temperature rise of about 0.1 °C to 2.5 °C depending on the experimental parameters.…”
Section: What Is the Expected Temperature Rise And How May It Affectmentioning
confidence: 99%
“…Gysbrechts et al (32) used these optical measurements to estimate light-induced thermal effects, but did not validate their estimates with in vivo measurements. Stujenske et al (35) performed temperature measurements in vivo to ascertain the effects of green light on neural tissue and found that the temperature increases predicted by models were higher than measured in vivo, underscoring the importance of in vivo measurements.…”
Section: Significancementioning
confidence: 99%
“…In general, the size of the light source, the fiber tip (which determines the focus or spread of light), and light intensity can be varied. With these parameters it is possible to calculate the heat produced by the light stimulation [125], and verify that tissue heating is limited to approximately 1°C-the value below which neural and hemodynamic activity are affected [126,127]. Thus, direct stimulations in the lesion area or peri-infarct area may have a negative effect on recovery.…”
Section: Benefits Of Optogeneticsmentioning
confidence: 99%